2007
DOI: 10.1002/app.26445
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(ether sulfone) nanofibers by gas‐jet/electrospinning

Abstract: Poly(ether sulfone) (PES) nanofibers were prepared by the gas-jet/electrospinning of its solutions in N,N-dimethylformamide (DMF). The gas used in this gasjet/electrospinning process was nitrogen. The morphology of the PES nanofibers was investigated with scanning electron microscopy. The process parameters studied in this work included the concentration of the polymer solution, the applied voltage, the tip-collector distance (TCD), the inner diameter of the needle, and the gas flow rate. It was found from exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 41 publications
(32 reference statements)
5
51
0
2
Order By: Relevance
“…The decrease in fiber diameters with increased airflow was confirmed through experiments carried out by the authors of Ref. 20. The awarded patents also prove the feasibility of upscaling electroblowing and its industrial use [21][22][23].…”
Section: Introductionmentioning
confidence: 76%
“…The decrease in fiber diameters with increased airflow was confirmed through experiments carried out by the authors of Ref. 20. The awarded patents also prove the feasibility of upscaling electroblowing and its industrial use [21][22][23].…”
Section: Introductionmentioning
confidence: 76%
“…It necessitates a gas jet device connected to the needle and is known as the gas-jet electrospinning technique [13,15,[116][117][118]. In this technique the needle of the spinning solution is encircled by the tube of the gas jet.…”
Section: Gas-jet Electrospinningmentioning
confidence: 99%
“…In this technique the needle of the spinning solution is encircled by the tube of the gas jet. Lin et al [116] studied the effect of ID and gas flow rate while keeping the other parameters fixed. They found that a smaller ID led to smaller average diameters, while the average diameter decreased monotonically as the gas flow rate increased.…”
Section: Gas-jet Electrospinningmentioning
confidence: 99%
“…For this reason, PES is often used as a membrane material in the biotechnological and pharmaceutical industries (Xu and Alsalhy Qusay 2004;Rahimpour et al 2010). Electrospinning of PES is mostly performed with single solvents such as dimethylformamide (DMF) and dimethylacetamide (DMAc) (Lin et al 2008;Babaeijandaghi et al 2010;Homaeigohar et al 2010), although solvent mixtures such as DMF:toluene (Ma et al 2009) or DMF:NMP (Yoon et al 2009;Tang et al 2009;Bui et al 2011) have also been attempted. The use of heated mixtures such as DMF:NMP solution is mainly aimed at wet spinning of PES nanofibers onto a carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different electrospinning parameters on the steady state was investigated and the formed nanofibers characterized. Currently, the literature describes electrospun PES fiber diameters with standard deviations ranging from 35 % to more than 50 % (Lin et al 2008;Ma et al 2009;Tang et al 2009;Homaeigohar et al 2010;Bui et al 2011). We also investigated whether the PES electrospun under steady state conditions gives more uniform nanofibers' diameters.…”
Section: Introductionmentioning
confidence: 99%